A Novel Approach for Efficient Data Sharing and Revocation with Data Access control - Banothu, Narsimha; Dayaker, P; Reddy, P. Bhaskara (International Journal of Computer Sciences and Engineering, 2025)
The novel paradigm of data outsourcing on the cloud is a double-edged sword. On the one hand, it frees data management owners and allows data owners to more easily share their data with targeted users. On the other hand, this poses new challenges in terms of privacy and security. In order to protect the confidentiality of data from the honest but curious cloud service provider, many works have been proposed to support data access control with precise rules. However, so far, no system is able to support both granular access control and the publication of time-sensitive data. In this article, integrating timed cryptography into Cipher text cryptographic encryption (CP-ABE) encryption, we propose a new control of time access and attributes on time-sensitive data for archiving. In the public cloud (called TAFC). Based on the proposed scheme, we also propose an efficient approach to designing policies to access the various access requirements for time-sensitive data. The indepth analysis of safety and performance shows that the proposed scheme is highly efficient and meets the security requirements for data storage in the public cloud